(untitled) (Marketing Jurnali, 2025)
This article analyzes the theoretical foundations of green marketing concepts and its impact on the environment and economy. The necessity, advantages and core principles of eco-friendly products and environmentally conscious brands are examined, and Patagonia is taken as a case example.